Analysis of Gross Motor Skills in Dance Activities for Children Aged 5 – 6 Years at the Pembina Tanjung Morawa State Kindergarten - Tia Ulfah; Kamtini (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to describe children's gross motor skills and dance activities in stimulating the gross motor skills of children aged 5-6 years at the Pembina Tanjung Morawa State Kindergarten. This research uses a qualitative descriptive research type. This research was carried out with the research subjects being 5 children aged 5-6 years consisting of 3 girls and 2 boys who took part in dance extracurricular activities at the Pembina Tanjung Morawa State Kindergarten. The data analysis techniques used are data collection, data reduction, data presentation and data verification. The results of the research show that children's gross motor skills in dance activities are seen from six aspects, namely 1) Speed, showing that children are able to move optimally, such as standing on tiptoes, 2) Coordination, children can combine all body movements at one time, 3) Speed, children are able to move as much as possible in a short time 4) Balance, shows the child is able to maintain his body in various positions, 5) Flexibility, the child can move his body as widely as possible, 6) Agility, shows the child moves and moves deftly. Of the five children who were studied, three of them showed results in gross motor skills in dance activities in aspects namely strength, coordination, speed, balance, flexibility and agility. One child in the aspects of coordination, balance, flexibility. Another child in the aspects of strength, coordination, balance, flexibility and agility.